Application of processing maps and numerical modelling for identification of parameters and limitations of hot forging process of 80MnSi8-6 steel - Wojtaszek, Marek; Lisiecki, Łukasz; Łukaszek-Sołek, Aneta; Korpała, Grzegorz; Zyguła, Krystian; Śleboda, Tomasz; Jabłońska, Magdalena Barbara; Prahl, Ulrich (Archives of Civil and Mechanical Engineering, 2023)
The processing maps developed by dynamic material modelling (DMM) method are now widely used in the design of hot forming processes. However, this applies to those processes that are relatively fast or are carried out under isothermal conditions, when it is possible to maintain the deformation parameters within the processing window. In the case of multi-stage free forging, the temperature successively decreases during subsequent operations and is increased during inter-process reheating. Under such conditions, processing maps in direct form are not applicable. The proposed solution is to implement the data obtained by the DMM method into calculations carried out by the finite element method (FEM). This approach leads to obtain the distributions of DMM parameters in the volume of the feedstock at successive forging stages. Selected results of a combined DMM/FEM analysis of a multi-stage hot forging process of 80MnSi8-6 steel are presented. The starting data for the analysis were the flow curves of this material, determined from compression tests. The processing maps were developed and processing windows were determined. The results of the DMM analysis were verified by microstructure observations. Data from the DMM analysis were implemented into QForm software using LUA scripts. An integrated FEM/DMM numerical analysis of the process of a multi-step hot free forging of an example product was performed. The geometry of the tools and a sequence of operations were developed. The distributions of the DMM parameters and the hot deformation activation energy in the forging volume after successive forging sequences were analyzed.